Reactive Nitrogen Species and Fibrinogen: Exploring the Effects of Nitration on Blood Clots - Francesca Nencini; Serena Borghi; Elvira Giurranna; Ilenia Barbaro; Niccolò Taddei; Claudia Fiorillo; Matteo Becatti (Antioxidants)
Reactive nitrogen species (RNS), particularly peroxynitrite (ONOO−), play a central role in post-translational modifications (PTMs) of proteins, including fibrinogen, a key component of the coagulation cascade. This review explores the structural and functional consequences of fibrinogen nitration, with a focus on its impact on clot formation, morphology, mechanical stability, and fibrinolysis. Nitration, primarily targeting tyrosine residues within functional domains of the Aα, Bβ, and γ chains, induces conformational changes, dityrosine crosslinking, and aggregation into high molecular weight species. These modifications result in altered fibrin polymerization, the formation of porous and disorganized clot networks, reduced mechanical resilience, and variable susceptibility to fibrinolysis. Moreover, nitrated fibrinogen may affect interactions with platelets and endothelial cells, although current evidence remains limited. Emerging clinical studies support its role as both a prothrombotic mediator and a potential biomarker of oxidative stress in cardiovascular and inflammatory diseases. Finally, we explore both pharmacological interventions, such as NOX inhibitors, and natural antioxidant strategies at counteracting fibrinogen nitration. Overall, fibrinogen nitration emerges as a critical molecular event linking oxidative stress to thrombotic risk.